All Days 2001
DOI: 10.2118/66553-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Low Viscosity Ester is Suitable for Drilling Fluids in Deepwater Applications

Abstract: High biodegradability and relatively low toxicity have long made esters universally recognized as the best base fluids for synthetic-based muds in regards to environmental performance. A major limiting factor in the use of ester-based fluids, particularly in deep water, is the inherently high kinematic viscosity, a condition that is magnified in the cold temperatures encountered in deepwater risers. These higher viscosities are believed to be especially critical in deepwater wells where lack of overburden caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…For instance, FAOEs can be employed in the deep-water drilling industry because of their excellent lubricity, high biodegradability, and low toxicity. Previous research suggested that C 8 fatty acid esters showed lower viscosities than their conventional counterparts over a broad temperature range, rendering them ideal fluids for address viscosity issues at increasing water depths . Their low viscosities also allow them to provide a wide range of mud weights, oil/water ratios, and high tolerances to solid contamination .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, FAOEs can be employed in the deep-water drilling industry because of their excellent lubricity, high biodegradability, and low toxicity. Previous research suggested that C 8 fatty acid esters showed lower viscosities than their conventional counterparts over a broad temperature range, rendering them ideal fluids for address viscosity issues at increasing water depths . Their low viscosities also allow them to provide a wide range of mud weights, oil/water ratios, and high tolerances to solid contamination .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Produced by esterification with another low-cost feedstock, n -octanol, which is the least expensive of the long-chain alcohols (C 8 –C 14 ), fatty acid n -octyl esters (FAOEs) have applications (as low-viscosity fluids) such as in modern two-stroke engines, cold-metal rolling, coolants for metal machinery, and drilling fluids for the marine oil industry . This low-viscosity lubricant has advantages of low toxicity, biodegradability, miscibility with various additives, oxidative stability, and the absence of undesirable impurities .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive testing designed to simulate deepwater drilling conditions indicated that the ester fluid would offer both technical and environmental advantages over other SBFs such as internal olefins. 8 In 2000, the fluid was field-tested on a GOM well in 3,669 ft of water. Data from the PWD tool demonstrated that the fluid did not cause high ECDs even when exposed to chilly riser temperatures.…”
Section: Regulatory Changes In the Gommentioning
confidence: 99%
“…In the early 1990s, ester-based drilling fluids were successfully applied in the North Sea of the United Kingdom. The oil field has achieved great success [5] [6] huge benefits [8]. However, the rheology of the second-generation synthetic-based drilling fluid is greatly affected by temperature [9].…”
Section: Introductionmentioning
confidence: 99%